Beispiel Nr: 16
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 2 x +4 y =4\\ -\frac{1}{2} x +3 y = 3 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} I \qquad 2 x +4 y =4\\ II \qquad -\frac{1}{2} x +3 y = 3 \\ \text{I nach y auflösen}\\ 2 x +4 y =4 \\ 2 x +4 y =4 \qquad /-2 x\\ 4 y =4 -2 x \qquad /:4 \\ y =1 -\frac{1}{2} x \\ \text{II nach y auflösen}\\ -\frac{1}{2} x +3 y =3 \\ -\frac{1}{2} x +3 y =3 \qquad /+\frac{1}{2} x\\ 3 y =3 +\frac{1}{2} x \qquad /:3 \\ y =1 +\frac{1}{6} x \\ \text{I = II}\\ 1 -\frac{1}{2} x =1 +\frac{1}{6} x \qquad /+\frac{1}{2} x /-1 \\ 1-1 =\frac{1}{6} x +\frac{1}{2} x \\ 0 =\frac{2}{3} x \qquad /:\frac{2}{3} \\ x=0 \\ \text{x in I}\\ y =1 -\frac{1}{2} \cdot 0 \\ y=1 \\ L=\{0/1\} \end{array} & \begin{array}{l} I \qquad 2 x +4 y =4\\ II \qquad -\frac{1}{2} x +3 y = 3 \\ \text{I nach x auflösen}\\ 2 x +4 y =4 \\ 2 x +4 y =4 \qquad /-4 y\\ 2 x =4 -4 y \qquad /:2 \\ x =2 -2 y \\ \text{II nach x auflösen}\\ -\frac{1}{2} x +3 y =3 \\ -\frac{1}{2} x +3 y =3 \qquad /-3 y\\ -\frac{1}{2} x =3 -3 y \qquad /:\left(-\frac{1}{2}\right) \\ x =-6 +6 y \\ \text{I = II}\\ 2 -2 y =-6 +6 y \qquad /+2 y /+6 \\ 2+6 =6 y +2 y \\ 8 =8 y \qquad /:8 \\ y=1 \\ \text{y in I}\\ x =2 -2 \cdot 1 \\ x=0 \\ L=\{0/1\} \end{array} \end{array} $